Pengaruh Pemberian Pupuk Limbah Organik Terhadap Pertumbuhan Dan Hasil Tanaman Mentimun (Cucumis Sativus L.) - Widiya Satriawi; Etik Wukir Tini; Achmad Iqbal (Jurnal Penelitian Pertanian Terapan, 2019)
Cucumber is one of the choices of horticultural commodities for farming activities. To increase the production of cucumber can be done by using organic waste fertilizers, such as pineapple peel waste and rice washing water. This research aims: 1) to know the best concentration of liquid organic fertilizer of pineapple peel waste for growth and yield of cucumber; 2) to know the best concentration of liquid organic fertilizer of rice washing water for growth and yield of cucumber; and 3) to know the best combination of concentration of liquid organic fertilizer of pineapple peel waste and liquid organic fertilizer of rice washing water for growth and yield of cucumber. The research was conducted at screen house located in Tambaksogra Village, Sumbang Sub-district, Banyumas Regency and the Laboratory Agronomy and Horticulture, Faculty of Agriculture, Jenderal Soedirman University, on Januari until June 2019. The experiment design used was Completely Randomized Block Design with 2 factors and 3 replication. The first factor was the concentration of liquid organic fertilizer of pineapple peel waste, namely 0, 10, 20, and 30 ml/l. The second factor was the concentration of liquid organic fertilizer of rice washing water, namely 0, 10, 20, and 30 ml/l. The results showed that: 1) the concentration 30 ml/l of liquid organic fertilizer of pineapple peel waste increased fruit weight per plant compared to the control treatment of 606,02 g : 45,48%, fruit length 15,99 cm : 9,22%, and fruit volume 163,87 ml : 13,37%; 2) the concentration liquid organic fertilizer of rice washing water did not increased the growth and yield of cucumber plants; and 3) the combination of concentrations liquid organic fertilizer of pineapple peel waste and rice washing water gave the same response to plant growth and yield.